Content based image search in openstack swift - Ali Uday, Mir Rownak; Islam Sakif, Md. Sadiqul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.